A vacuum distillation process for separation of antimony trisulfide and lead sulfide from jamesonite. (June 2021) - Zhou, Zhengen; Liu, Dachun; Xiong, Heng; Wang, Chengyan; Ma, Baozhong; Wei, Liu; Chen, Yongqiang; Huang, Kun
Abstract: Jamesonite is an important complex antimony mineral which treated by conventional methods have shortcomings, such as sulfur dioxide emission and low antimony and lead recovery. This study applied vacuum metallurgy technology to treat jamesonite. The vacuum decomposition behavior of jamesonite (Pb4 FeSb6 S14 ) was investigated, and a two-step vacuum distillation process of separation of antimony trisulfide (Sb2 S3 ) and lead sulfide (PbS) from jamesonite was developed. First of all, the decomposition behavior of Pb4 FeSb6 S14 under vacuum condition was comprehensively studied. The results indicate it decompose into Sb2 S3, PbS and FeS at 823 K under vacuum condition, then, Sb2 S3 and PbS volatilize at different temperatures. Based on above results, we investigated the effects of vacuum distillation temperature and time on the recovery of Sb2 S3 and PbS as well as the effects of temperature on the purity of them. The results indicate that the optimal temperature for separating Sb2 S3 and PbS are 923 K and 1173 K, respectively. Under optimal conditions, up to 98% of Sb2 S3 with a purity of 99.17% and up to 99.5% of PbS with a purity of 98.7% could be recovered. Highlights: Vacuum decomposition temperature and mechanism of Pb4 FeSb6 S14 were tested and revealed. A two-step vacuum distillation process of separating Sb2 S3 and PbS from jamesonite was developed. The optimal experimental conditions of Sb2 S3 and PbS recovery were determined. This study provides a eco-friendly method to separate lead and antimony from jamesonite.